Research data management : practical strategies for information p rofessionals - Ray, Joyce M. (West Lafayette, Indiana : Purdue University Press, 2014)
"It has become increasingly accepted that important digital data mus t be retained and shared in order to preserve and promote knowledge, ad vance research in and across all disciplines of scholarly endeavor, and maximize the return on investment of public funds. To meet this challe nge, colleges and universities are adding data services to existing inf rastructures by drawing on the expertise of information professionals w ho are already involved in the acquisition, management and preservation of data in their daily jobs. Data services include planning and implem enting good data management practices, thereby increasing researchers' ability to compete for grant funding and ensuring that data collections with continuing value are preserved for reuse. This volume provides a framework to guide information professionals in academic libraries, pre sses, and data centers through the process of managing research data fr om the planning stages through the life of a grant project and beyond. It illustrates principles of good practice with use-case examples and i lluminates promising data service models through case studies of innova tive, successful projects and collaborations"--
The policy and institutional framework / James L. Mullins -- Data go vernance : where technology and policy collide / MacKenzie Smith -- The use of life cycle models in developing and supporting data services / Jake Carlson -- Data management assessment and planning tools / Andrew Sallans and Sherry Lake -- Trustworthy data repositories : the value an d benefits of auditing and certification / Bernard F. Reilly, Jr. and M arie E. Waltz -- Copyright, open data, and the availability-usability g ap : challenges, opportunities, and approaches for libraries / Melissa Levine -- Metadata services / Jenn Riley -- Data citation : principles and practice / Jan Brase, Yvonne Socha, Sarah Callaghan, Christine Borg man, Paul Uhlir, and Bonnie Carroll -- Assimilating digital repositorie s into the active research process / Tyler Walters -- Partnering to cur ate and archive social science data / Jared Lyle, George Alter, and Ann Green -- Managing and archiving research data : local repository and C loud-based practices / Michele Kimpton and Carol Minton Morris -- Chron opolis repository services / David Minor, Brian E. C. Schottlaender, an d Ardys Kozbial -- Evaluating a complex project : DataONE / Suzanne All ard -- What to measure? : toward metrics for research data management / Angus Whyte, Laura Molloy, Neil Beagrie, and John Houghton -- An insti tutional perspective on data curation services : a view from Cornell Un iversity / Gail Steinhart -- Purdue University Research Repository : co llaborations in data management / D. Scott Brandt -- Data curation for the humanities : perspectives from Rice University / Geneva Henry -- De veloping data management services for researchers at the University of Oregon / Brian Westra.
Includes bibliographical references and index.
Keywords: Information storage and retrieval systems; Research -- Information services; Data libraries; Electronic information resources -- Management; Digital libraries -- Management; Libraries and scholars; Communication in learning and scholarship -- Technological innovatio ns; Institutional repositories; BUSINESS & ECONOMICS / Information Management; REFERENCE / Research